Exploring the genetic diversity and population structure of Mobula birostris in two key aggregation zones in the Eastern Tropical Pacific - Rojas López, Karla E. (2022)
The giant manta ray Mobula birostris is the largest ray species in the world. Little isknown about its genetic composition in key aggregation sites such as the Galapagos Islands andIsla de la Plata, near the province of Manabi in mainland Ecuador. This study aimed to determinethe genetic diversity and population structure of M. birostris in these 2 locations to better understand its connectivity and distribution in Ecuadorian oceanic waters and to assist in its conservation and appropriate management. A total of 127 samples from mainland Ecuador (2013−2018)and 21 samples from Galapagos (2019) were collected and analyzed using 8 microsatellite loci.Results showed a moderately high level of genetic diversity for giant manta rays from both sites(mainland Ecuador He = 0.72; Galapagos He = 0.66). Population structure analyses suggests thepresence of 2 different populations in the Galapagos and mainland Ecuador. The different geneticcompositions found for each location could be associated with the displayed resident behavior,linked to the formation of upwelling systems caused by oceanic currents that bring nutrient-richwaters to both sites year-round. Our genetic connectivity analysis confirmed low gene flowbetween these 2 locations, further rejecting the hypothesis of a single panmictic population of M.birostris in Ecuador. Taken together, these results provide valuable information about the geneticcomposition and diversity of the giant manta ray, an Endangered species which has been scarcelystudied in the Eastern Tropical Pacific.